Network Security: A study on Emergency security signal technology for safety (International Journal of Engineering and Computer Science, 2014)
It is very recent technology which is mainly used in network security, networking, computing, and distributed computing. These types of service reduce the information technology overhead for end users. It is reliable to handle and provide flexibility and on-demand services. This service provides reliability even when we are traveling. It becomes an important task to security for the devices that we are dependent so much. This device is used to provide safety signal. To handle this types of service a new service device come into use that is SOS. SOS means stay safe! The SOS signals come from Morse code distress signal. The SOS term use for various phases. The Morse code distress signals are firstly replaced with Global Maritime Distress Safety system. This paper, is tell us about security signals used in emergency for safety. It gives a view on various security services for safety that are replaced with old one.